Cenozoic exhumation history of South China: A case study from the Xuefeng Mt. Range. (January 2018) - Wang, Yannan; Zhang, Jin; Zhang, Beihang; Zhao, Heng
Graphical abstract: Highlights: Exhumation in South China occurred during the Cenozoic. There is no evidence for the existence of a previously thought Pan-Yangtze Basin in Cretaceous. The subduction of the Pacific Plate beneath the Eurasian Plate caused the early Cenozoic uplift. Abstract: New apatite fission track (AFT) dating was applied to the Xuefeng Mt. Range and Yuanma Basin to constrain the Cenozoic exhumation process of the southeastern Yangtze Block, South China. The analyzed samples in this study have AFT ages ranging from 27.9 ± 2.5 to 61.5 ± 5.9 Ma, which are younger than the deposition or crystallization ages of the host rocks. The AFT analysis and thermal history modeling indicate that both the Xuefeng Mt. Range and the Yuanma Basin underwent significant exhumation during the early Cenozoic (ca. 60–40 Ma). These samples were rapidly exhumed to near the surface during this period. Our results suggest that an important tectonic event occurred along or near regional fault zones (e.g., the Qinhang Fault) in South China during the early Cenozoic (ca. 60–40 Ma). However, it is difficult to relate this event to the Eastern Sichuan fold belt, which is much older and is characterized by large-scale folding and thrusting. Combined with fieldwork in the Yuanma, Xupu, and Xinning basins, we refute the Cretaceous "Pan-Yangtze Basin" that was proposed to have been separated by the uplifted Xuefeng Mt. Range after the Late Cretaceous. The exhumation stage from ca. 60 Ma to 40 Ma was an important period during which plate movements across the eastern Asian and Pacific regions were reorganized. The early Cenozoic tectonothermal event in South China can be attributed to a change in the direction and speed of the subduction of the Pacific Plate beneath the Eurasian Plate. An Oligocene-Miocene cooling event was also recorded in the eastern Xuefeng Mt. Range, which we tentatively attribute to the activity of dextral faults in this area as a far-field effect of the collision between the Indian and Eurasian plates.